2020
DOI: 10.1002/ejp.1640
|View full text |Cite
|
Sign up to set email alerts
|

Conduction velocity of the cold spinal pathway in healthy humans

Abstract: Neurophysiological assessment of the spinothalamic system currently relies on noxious heat-and warm-mediated evoked potential recordings related to Aδ-and C-fibres, using laser and contact heat stimulation (Iannetti et al., 2003; Wydenkeller, 2008). A new device based on micro-Peltier elements that is able to produce steep cooling ramps up to 300°C/s has been developed to activate selectively cold-mediating fibres (De Keyser, van den Broeke, Courtin, Dufour, & Mouraux, 2018). This tool, which provides rapid an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Particularly, examining the distal lower extremities in elderly subjects remains a challenge ( 31 ). While improvements in CEP recording could be achieved with advanced thermal stimulators (featuring steep cooling ramps and low target temperatures ( 35 , 75 ), for now, only the Medoc thermal stimulator possesses a CE certificate as a diagnostic tool on patients in clinical routine, facilitating their application in both research and clinical diagnostics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Particularly, examining the distal lower extremities in elderly subjects remains a challenge ( 31 ). While improvements in CEP recording could be achieved with advanced thermal stimulators (featuring steep cooling ramps and low target temperatures ( 35 , 75 ), for now, only the Medoc thermal stimulator possesses a CE certificate as a diagnostic tool on patients in clinical routine, facilitating their application in both research and clinical diagnostics.…”
Section: Discussionmentioning
confidence: 99%
“…This is where CEPs might step in: The advantages of CEP assessment as a non-invasive method to measure small fibers and their central pathways are comparable to those of LEPs, but with the upside of a pain-free examination. A study on the conduction velocity of the cold spinal pathway even suggested that CEPs may represent an alternative to LEPs ( 75 ).…”
Section: Discussionmentioning
confidence: 99%
“…In an effort to improve the technique and make it reliable enough for clinical use, important questions have been addressed in the recent years, including the influence of skin type, fixed or variable probe position, inter-stimulus interval and aging (De Keyser et al, 2018;Hüllemann et al, 2016Hüllemann et al, , 2019Leone et al, 2019Leone et al, , 2020Lithfous et al, 2022;Rosner et al, 2019;Scheuren et al, 2022). While these studies substantiate the potentialities of CEPs as a diagnostic tool, clinical studies in patients with NP have been so far limited to selective case reports.…”
Section: Introductionmentioning
confidence: 99%